TLR4 supports the expansion of FasL+CD5+CD1dhi regulatory B cells, which decreases in contact hypersensitivity. (July 2017) - Wang, Keng; Tao, Lei; Su, Jianbing; Zhang, Yueyang; Zou, Binhua; Wang, Yiyuan; Zou, Min; Chen, Nana; Lei, Linsheng; Li, Xiaojuan
Highlights: TLR4 ligation could induce FasL expression in CD5 + CD1d hi Breg, which could be independent of IL-10 production. TLR4 ligation activated FasL expression in CD5 + CD1d hi Breg could be reduced by NF-κB and NF-AT inhibitor. TLR4 ligation activated CD5 + CD1d hi Breg could suppress CD4 + T cell proliferation partly via FasL. FasL + CD5 + CD1d hi Breg reduced in contact hypersensitivity (CHS). Abstract: Certain B cells termed as "regulatory B cells" (Bregs) can suppress the ongoing immune responses and a splenic CD5 + CD1d hi Breg subset identified earlier was shown to exert its regulatory functions through secretion of IL-10. Though FasL expression is an alternative mechanism of immune suppression used by B cells, little is known about the FasL expressing CD5 + CD1d hi Bregs. In this study, we isolated splenocytes or splenic CD19 + B cells and compared the efficiency of toll-like receptor(TLR)4 ligand (lipopolysaccharide) with TLR9 ligand (CpG), anti-CD40 and TLR9 ligand (CpG) plus anti-CD40 on the FasL expression of splenic CD5 + CD1d hi Bregs by flow cytometry. FasL expression in CD5 + CD1d hi B cells was rapidly increased after TLR4 ligation. Intriguingly, anti-CD40 and CpG plus anti-CD40 combinations failed to stimulate FasL expression in CD5 + CD1d hi B cells although the IL-10 production was up-regulated in this subset. In addition, LPS and other B10-cell inducers increased the expression of surface molecules like CD86 and CD25, which are correlated to the regulatory functions of B cells. Furthermore, NF-κB and NF-AT inhibitors decreased the TLR4-activated FasL expression in CD5 + CD1d hi B cells. Then we sorted splenic CD5 + CD1d hi Bregs using flow cytometry and found that TLR4-activated CD5 + CD1d hi Bregs suppressed the proliferation of CFSE-labeled CD4 + T cells in vitro, which was partly blocked by anti-FasL antibody. In oxazolone-sensitized mice having contact hypersensitivity, FasL expression in splenic CD5 + CD1d hi B cells was decreased compared to the control group after TLR4 ligation. Our findings suggest that the regulatory function of CD5 + CD1d hi B cells could be partly mediated by Fas-FasL pathway and this FasL expressing CD5 + CD1d hi Bregs might participate in the regulation of inflammatory diseases.